Over expression of circulating miR-155 predicts prognosis in diffuse large B-cell lymphoma. (July 2018) - Ahmadvand, Mohammad; Eskandari, Mahsa; Pashaiefar, Hossein; Yaghmaie, Marjan; Manoochehrabadi, Saba; Khakpour, Golnaz; Sheikhsaran, Fatemeh; Montazer Zohour, Mostafa
Highlights: MicroRNAs expression could be important to leukemia treatment. miR-155 is upregulated in DLBCL patients with compared to healthy individuals Upregulation of miR-155 is correlated with poor overall survival in DLBCL patients. Abstract: Introduction: The expression patterns of microRNAs in plasma are involved in potential biomarkers for several diseases. The goal of this study was to explore the expression level of miR-155 in diffuse large B-cell lymphoma (DLBCL) and its clinical significance. Materials and methods: We used qRT-PCR to assess the peripheral blood plasma of 40 DLBCL patients for the expression of miRNA-155. The median of miR-155 expression divided the DLBCL patients into miR-155 low-expression (miR-155 low ) and miR-155 high-expression (miR-155 high ) groups. Results and discussion: We found that plasma miR-155 expression was significantly up-regulated in patients with DLBCL (median expression value: 4.29, range: 1.52–27.86) compared to healthy individuals (median expression value: 2.14, range: 0.29–10.56, P < 0.002). Moreover, DLBCL cases with an elevated level of miR-155 had shorter overall survival (median 9 vs. 13 months, P = 0.043) than those with a lower miR-155 expression.